Effects of Grape Downy Mildew on Photosynthesis of 'Red Globe' Grape Leaves under High Temperature Stress. Issue 1 (31st December 2022) - Yang, Haibo; Gao, Tiantian; Li, Qingliang; Tan, Wei; Sun, Xia; Wang, Deya; Cao, Hui
ABSTRACT: Grape downy mildew is a major grape disease that typically occurs when grape leaves are subjected to high temperature. In this study, downy mildew incidence in 'Red Globe' grape was investigated. To clarify the effects of grape downy mildew on grape leaves under high-temperature stress. Grape downy mildew infestation and high-temperature treatment alone or combinations were applied to 'Red Globe' grape. The gas exchange and chlorophyll fluorescence parameters of grape leaves were measured. The results showed that logistic growth period of grape downy mildew in the Jinzhong, China was from July 20 to August 10. After the combined stress of high temperature and grape downy mildew, photosynthetic rate ( Pn ), stomatal conductance ( G s ), intercellular carbon dioxide concentration ( C i ), maximum photochemical efficiency( Fv/Fm ), actual photochemical efficiency( ΦPSII ), and performance index on absorption basis ( PIABS ) of grape leaves were all decreased more than the sum of those indexes under the two stresses individually. At 28°C, the damage of downy mildew had no significant effect on the degree of photosystem closure of leaves, but it was significantly increased with the combined stresses. The electron transfer efficiency from photosystem II to photosystem I was decreased significantly under the combined stresses. Under 38°C high-temperature stress, the energy dissipated per active reaction center of the leaves affected by grape downy mildew was significantly increased. High temperature aggravated adverse effects of downy mildew on the structure and function of photosystem II ( PSII ) of grape leaves and then further exacerbated reduction of photosynthesis caused by heat stress.